Reframing A Self-Organized Learning Environment (SOLE) to Accommodate Indonesian EFL Students’ Learning Loss - Shofie Nurul Azizah; Fahry Rizaldy Putra (Institut of Shanti Bhuana, 2024)
In the wake of the COVID-19 lockdown, students have faced heightened learning loss, attributed to factors such as inadequate learning methods, restricted access to education, decreased instructional time, and emotional stressors. Particularly affected is English language learning, prompting the need for effective remedies. This study proposes the implementation of new Self-Organized Learning Environments (SOLEs) as a strategic response to mitigate learning setbacks, especially in post-pandemic contexts. Employing a systematic review of relevant literature and employing established methodologies for position paper composition, this research undertakes a comprehensive analysis of SOLEs' effectiveness in nurturing students who experienced learning loss. Divided into three focal areas, the study explores the evolving new role of teachers within SOLEs, the integration of SOLEs in English as a Foreign Language (EFL) pedagogy, and the utilization of digital applications to enhance language-focused SOLE practices. Through this multifaceted analysis, the study aims to offer innovative insights and actionable recommendations for addressing learning loss and fostering resilient educational strategies in the aftermath of the pandemic.The results of this study contribute valuable knowledge to the ongoing discourse on educational recovery, with implications for educators, policymakers, and stakeholders invested in creating adaptive and effective learning environments.